The impact of Ukraine's shadow economy development on the macroeconomic indices under conditions of globalization - Inga Miroshnychenko (Cхід, 2013)
In the article under consideration the trends of impact of the shadow economy growth process on the basic macroeconomic indices of the state development in the context of the world tendencies are investigated. The views of home and foreign scholars on the nature and factors of the shadow economy development are analyzed. The experience of international organizations activity aimed at struggling with illegal funds laundering is studied. The condition and dynamics of Ukraine's GDP of 2005-2012 are observed. The variety-level model of the range and level of shadow economy reduction by means of improving the methodical approaches of management mechanism of this process at the regional, national (state), international and world (global) levels is proposed.